On the Application of Rational Choice Theory to Financial Reporting Controversies: A Comment on Cushing. - Bejan, Mary (The Accounting Review, 1981)
This article comments on a 1977 article by researcher B.E. Cushing on financial reporting. Using the article as a point of departure, it attempts to clarify what can and cannot be said about the individual's choice to "use" information, public or private, the potential effects of its public availability, and what factors are relevant to predicting the welfare impact of an accounting policy change. Cushing attempts to work in a general equilibrium framework to evaluate proposed changes in accounting standards. He defines an accounting principle to be optimal if "the resulting financial statements enable all users to achieve an expected payoff which is greater than or equal to the corresponding payoff under any alternative accounting principle, holding the principles used in all other areas of controversy constant." A central contention in Cushing's article is that the assumptions of individual rationality and publicly available information allow one to consider financial statement users only.